How openness to experience drives R&D staff’s innovative behavior: a nonlinear mediation and moderation perspective on flow experience and emotional intelligence - Liu, Yanqiong; Sun, Zhaogang (Frontiers in Psychology, 2025)
IntroductionOpenness to experience is widely recognized as a driver of innovation, yet how flow experience mediates this relationship and whether emotional intelligence (EI) moderates it remain underexplored.MethodsThis study investigates the nonlinear mediating role of flow between openness and innovation behavior, and EI’s moderating effect, using quantitative data from 475 R&D professionals (male, 75.16%; female, 24.84%).ResultsResults reveal a curvilinear mediation: moderate flow enhances innovation, but excessive flow diminishes it. EI buffers this relationship, enabling sustained innovation under high flow intensity.DiscussionThe findings highlight the need to manage flow dynamics and underscore EI as a critical factor for fostering innovation in R&D contexts, offering practical insights for organizational creativity management.